Understanding Meal Choices in Young Adults and Interactions with Demographics, Diet Quality, and Health Behaviors: A Discrete Choice Experiment. Issue 8 (24th May 2021) - Livingstone, Katherine M; Abbott, Gavin; Lamb, Karen E; Dullaghan, Kate; Worsley, Tony; McNaughton, Sarah A
ABSTRACT: Background: Our understanding of meal choices is limited by methodologies that do not account for the complexity of food choice behaviors. Discrete choice experiments (DCEs) rank choices in a decision-making context. Objectives: This study aimed to rank the relative importance of influences on meal choices in young adults and examine interactions by subgroups. Methods: Adults (18–30 y) living in Australia were recruited via social media to complete an Internet-based DCE and survey. Participants were presented with 12 choice sets about a typical weekday meal, consisting of 5 attributes (taste, preparation time, nutrition content, cost, and quality). Diet quality (Dietary Guideline Index) was calculated from brief dietary questions. Conditional logit models ranked meal attributes, including interactions by sex, education, area-level disadvantage, diet quality, and weight status. Results: In total, 577 adults (46% female, mean ± SD age 23.8 ± 3.8 y) completed the DCE and survey. Nutrition content was the most important influence on meal choice (B: 1.48; 95% CI: 1.31, 1.64), followed by cost (B: –0.75; 95% CI: –0.87, –0.63), quality (B: 0.58; 95% CI: 0.49, 0.67), taste (B: 0.55; 95% CI: 0.45, 0.65), and preparation time (B: –0.42; 95% CI: –0.52, –0.31). Females, those with higher diet quality, and those with a BMI (in kg/m 2 ) <25 had higher preferences for better nutrition content. Females had higher preferences for better taste and lower preferences for higher-cost meals. Participants with higher education had higher preferences for better nutrition content. Participants living in higher area-level disadvantage areas had higher preferences for longer preparation time. Conclusions: Nutrition content was the most important influence on young adults' meal choices. Preferences differed by sex, socioeconomic position, diet quality, and weight status. Findings show the suitability of DCEs for understanding food choice behaviors in young adults and support the need for meal-based interventions to be tailored according to demographic and health characteristics.